2005
DOI: 10.1159/000090095
|View full text |Cite
|
Sign up to set email alerts
|

Articulatory Planning Is Continuous and Sensitive to Informational Redundancy

Abstract: This study investigates the relationship between word repetition, predictabil-ityfrom neighbouring words, and articulatory reduction in Dutch. For the sevenmost frequent words ending in the adjectival suffix -lijk, 40 occurrences were ran-domlyselected from a large database of face-to-face conversations. Analysis ofthe selected tokens showed that the degree of articulatory reduction (as measuredby duration and number of realized segments) was affected by repetition, pre-dictabilityfrom the previous word and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(120 citation statements)
references
References 21 publications
6
112
1
1
Order By: Relevance
“…While Goffman s account of prosodic marking is predominantly a speaker-oriented one concerned with the speaker s feelings at the time of the repair Levelt Cutler s (1983) account is more listener-oriented in this account the speaker produces informative discourse content prominently for the listener s benefit This is consistent with the recurrent finding in phonetic studies that new, unpredictable or otherwise important information is more likely to be produced with prosodic salience, emphasis or hyperspeech than old predictable or unimportant information based on speakers estimations of listeners knowledge and general intelligibility (Lindblom 1996, Baker & Bradlow 2000, Aylett & Turk 2004, Pluymaekers et al 2005, Smiljanić "radlow 2009, Seyfarth 2014. The reasoning in relation to repair is made explicit by Geluykens who suggests unfortunately without elaboration that in a subtype of repair in which a pronominal reference is replaced with a full noun it is important that this reparans gets some prosodic prominence, to facilitate comprehension for the hearer, and thus to ensure the resolving of the referential problem Studies focusing specifically on the relationship between prosody and information status (see Calhoun 2010, Ito & Speer 2011and Genzel et al 2014 for recent reviews) support this reasoning but to my knowledge, none has investigated repair.…”
Section: Why Mark a Repair?supporting
confidence: 66%
“…While Goffman s account of prosodic marking is predominantly a speaker-oriented one concerned with the speaker s feelings at the time of the repair Levelt Cutler s (1983) account is more listener-oriented in this account the speaker produces informative discourse content prominently for the listener s benefit This is consistent with the recurrent finding in phonetic studies that new, unpredictable or otherwise important information is more likely to be produced with prosodic salience, emphasis or hyperspeech than old predictable or unimportant information based on speakers estimations of listeners knowledge and general intelligibility (Lindblom 1996, Baker & Bradlow 2000, Aylett & Turk 2004, Pluymaekers et al 2005, Smiljanić "radlow 2009, Seyfarth 2014. The reasoning in relation to repair is made explicit by Geluykens who suggests unfortunately without elaboration that in a subtype of repair in which a pronominal reference is replaced with a full noun it is important that this reparans gets some prosodic prominence, to facilitate comprehension for the hearer, and thus to ensure the resolving of the referential problem Studies focusing specifically on the relationship between prosody and information status (see Calhoun 2010, Ito & Speer 2011and Genzel et al 2014 for recent reviews) support this reasoning but to my knowledge, none has investigated repair.…”
Section: Why Mark a Repair?supporting
confidence: 66%
“…Aylett and Turk (2006) show that syllable nuclei are shorter when they are locally predictable from context. Similar studies demonstrate the same for other levels of linguistic representation, such as consonants, morphemes, and words (Jurafsky et al 2001;van Son and Pols 2003;Pluymaekers et al 2005;van Son and van Santen 2005). Other studies link local predictability to syntactic planning (Levy and Jaeger 2007;Jaeger 2010) and use it to provide a basis for markedness (Hume 2008).…”
Section: Local Predictability Accountsmentioning
confidence: 61%
“…Similarly, different lexicons would cause segment predictability to be different in each language. Below the word level, several information theoretic factors such as frequency and predictability have been shown to affect segment, syllable, and morpheme duration and reduction Turk 2004, Aylett andTurk 2006;van Son and van Santen 2005;Pluymaekers et al 2005; among others). At the word level, related work found that frequent and predictable words tend to have shorter duration (Jurafsky et al 2001;Bell et al 2009;among others).…”
Section: What Determines Language-specific Duration and Deletion?mentioning
confidence: 99%
“…In line with cascaded flow of information, studies of spontaneous speech corpora have found frequency effects on articulation durations (Gahl, 2008;Pluymaekers, Ernestus, & Baayen, 2006). In single word production, a longer duration of the initial phoneme has been reported for words entailing irregular vowel pronunciation, compared to words with a regular vowel pronunciation (Kawamoto, Kello, Jones, & Bame, 1998).…”
Section: Introductionmentioning
confidence: 93%